Sex-specific starvation tolerance of copepods with different foraging strategies. (28th March 2018) - Holm, Mark Wejlemann; Rodríguez-Torres, Rocío; van Someren Gréve, Hans; Hansen, Benni Winding; Almeda, Rodrigo
Abstract: Planktonic copepods have sexual dimorphism that can lead to differences in starvation tolerance between genders. Additionally, mating may be energetically costly and thus reduce starvation tolerance. We investigated the influence of sexual dimorphism and mating on starvation tolerance of copepods with different feeding behaviours: Oithona nana (ambusher), Temora longicornis (feeding-current feeder) and Centropages typicus (cruiser). Males of C. typicus and O. nana had a starvation tolerance lower than females, whereas T. longicornis had a similar starvation tolerance between genders. Only O. nana males and females had reduced starvation tolerance when both genders were incubated together, which suggests that mating activities in ambushers have an energetic cost higher than in active feeding copepods. C:N ratios showed a non-significant difference between genders, which indicates that gender differences in starvation tolerance are not due to dissimilarities in lipid reserves. Gender differences in starvation tolerance can be partially explained by body size differences between sexes. This indicates a minor influence of mate-seeking behaviour on male starvation tolerance, likely due to reduced mate-searching behaviour under prolonged starvation. Our results demonstrate that sexual dimorphism can result in different starvation tolerance between copepod genders and that a negative effect of mating on starvation tolerance depends on the foraging strategy.